CCNA Guide to Cisco Networking - Cannon, Kelly
CCNA Guide to Cisco Networking, Third Edition provides comprehensive coverage of Cisco networking concepts, and serves as an ideal guide to prepare for the CCNA Certification Exam #640-801. This new edition presents the basics of networking, and covers the steps to configure Cisco routers for a variety of tasks. Over 50 hands-on labs are included in this new text and all concepts are reinforced with challenging real-world review questions